Sustainable Utilization of Local Natural Aggregates for Eco-Friendly Concrete Production: Integrating Geospatial and Regional Economic Data in West Java, South Sumatra, and South Sulawesi - Anugrah; Erny; Erniati Bachtiar; Arman Setiawan; Rita Hardianti Aris (Structures, Infrastructure, Planning, Implementation, and Legislation, 2025)
This study tackles the persistent environmental and economic complexities associated with conventional concrete manufacturing by establishing a novel sustainable production framework. This framework strategically integrates geospatial data on local aggregate reserves with key regional economic variables, focusing specifically on West Java, South Sumatra, and South Sulawesi as representative study areas in Indonesia. Leveraging Geographic Information System (GIS) technology and official statistics from the Geospatial Information Agency (BIG), alongside regional economic indices from the Central Statistics Agency (BPS), the investigation meticulously analyzed the spatial arrangement of high-quality aggregates, material price fluctuations, and crucial logistics expenditures. A multiple linear regression model was employed for quantitative analysis, which decisively revealed that aggregate pricing (=0.62, p < 0.001) and logistics expenses (=0.31, p < 0.05) are the predominant cost drivers in sustainable concrete production, whereas aggregate technical quality contributes a smaller, measurable influence (=0.09, p > 0.05). The exceptional coefficient of determination (R2=0.89) substantiates the model's predictive power and its practical utility for cost management and optimization within eco-friendly concrete systems. Ultimately, this research emphasizes the critical necessity of converging environmental, technical, and economic data for effective resource stewardship. It also proposes future scholarly endeavors should focus on integrating real-time monitoring and advanced digital supply chain technologies to further bolster the sustainability credentials of the domestic construction industry.